Performance evaluation and optimization of simultaneous phosphorus and nitrogen removal from anaerobically digested liquid-dairy-manure using an intermittently-aerated-extended-idle sequencing batch reactor - Asghar, Sehrish; Chen, Lide; He, B. Brian (Frontiers in Sustainable Food Systems, 2023)
Wastewater from confined dairy operations requires efficient treatment to reduce its potential to pollute the surrounding environments. In this study, a novel intermittently-aerated-extended-idle sequencing batch reactor (IA-EI SBR) process was developed, evaluated, and optimized for simultaneously removing phosphorus (P) and nitrogen (N) from anaerobically digested liquiddairy-manure (ADLDM) with lower carbon-to-nutrient-ratios. Four influential operating parameters including cycle-time of 5-9 h, intermittent-aeration strategy of 10-50 min/h, two feedphases of 6-30 min, and idle-phase of 40-120 min were statistically analyzed using centralcomposite design coupled with response-surface methodology for optimal removal efficiencies of ortho-phosphorus (%OPᵣₑₘₒᵥₐₗ), total-phosphorus (%TPᵣₑₘₒᵥₐₗ), ammonia-nitrogen (%NH3-Nᵣₑₘₒᵥₐₗ), total-nitrogen (%TNᵣₑₘₒᵥₐₗ), and chemical oxygen demand (%CODᵣₑₘₒᵥₐₗ). Results showed that the interactions of cycle time-idle phase, and aeration strategy-feed phases were significant in affecting %TPᵣₑₘₒᵥₐₗ (p-value ≤0.005). The synergistic effect of aeration strategy-idle phase was significant for %TNᵣₑₘₒᵥₐₗ and %CODᵣₑₘₒᵥₐₗ (p-value ≤ 0.006), while the cycle time-feed phases interaction had significant effect on %NH3-Nᵣₑₘₒᵥₐₗ. The maximum simultaneous nitrificationdenitrification (SND) efficiency of 85.7% was recorded under influent COD and TN loading of 3999.2 and 785.7 mg L -1 at 30 min/h aeration time in 7 h. The quadratic regression models based on statistical analysis of the experimental results adequately described the IA-EI SBR performance and showed that the applied levels of operating parameters were highly correlated with all five responses (p-value ≤ 0.030). Operating conditions for optimal IA-EI SBR process efficiency determined by desirability analysis were cycle-time of 8 h, intermittent-aeration strategy of 36 min/h, feed-phases of 24 min, and idle-phase of 100 min. Under these optimal conditions, the corresponding removal efficiencies for OP, TP, NH3-N, TN, and COD of 82.64%, 95.82%, 92.92%, 73.84%, and 90.94%, respectively, were achieved in validation experiments.